Conjuring criminals: Sympathetic magic and bureaucratic paperwork in a Brazilian juvenile prison. (1st February 2022) - DRYBREAD, K.
ABSTRACT: By compiling official paperwork, bureaucrats in institutional settings effectively make their clients into the particular "types" of subjects best suited to preestablished institutional interventions. The efficacy of such paperwork stems from bureaucrats' unspoken—and perhaps unacknowledged—belief in sympathetic magic, or a person's ability to transform another person or object by working on a representation of them (in this case, their institutional case file). The practice of sympathetic magic via official paperwork is particularly pervasive in disciplinary settings, like prisons, where institutional imperatives and cultural biases encourage professionals to substitute documentation for face‐to‐face interactions with their clients. How such magic works in practice becomes evident in an examination of case files belonging to adolescents incarcerated in a Brazilian juvenile prison during the first decade of the 21st century. In this case, each document added to an incarcerated individual's case file contributes to transforming him into an irredeemable criminal. [ bureaucracy, magic, documents, documentation, crime, criminalization, prison, Brazil ] RESUMO: Ao compendiar documentação oficial, burocratas em ambientes institucionais acabam por fazer de seus clientes "tipos" particulares de sujeitos mais adequados para intervenções institucionais. A eficiência de tal documentação vem de crenças que não são ditas—e talvez nem reconhecidas—de tais burocratas na mágica simpatética, ou na capacidade de uma pessoa de transformar outra ou um objeto por meio de sua representação (nesse caso, sua documentação institucional). A prática da mágica simpatética via papelada oficial é particularmente generalizada em ambientes disciplinares como prisões, onde imperativos institucionais e preconceitos culturais dão força aos profissionais para substituir documentação pela interação pessoal com seus clientes. O modo como tal mágica ocorre na prática se torna evidente quando se examinam casos de adolescentes encarcerados numa unidade de internação brasileira durante a primeira década do século XXI. Nesse caso, cada documento acrescentado ao caso de um "adolescente infrator" contribui para transformá‐lo em um criminoso irrecuperável. [ burocracia, mágica, documentos, documentação, crime, criminalização, prisão, Brasil ]